(untitled) (Heritage, 2021)
The topic of this paper is the analysis of the officer’s corps of the Serbian State Guard in Kosovska Mitrovica district. The introductory part explains the changes in formation, senior staff and the subordination of this collaborationist military formation in the mentioned area. In the main part of the work, based on the files of 43 officers, who served at some time in the occupation in aforementioned district, their structure is presented according to nationality, religion, place of birth, education, marital and family status. Also, short official biographies of all the officers examined were also given. The article is written on the basis of the original and published material, primarily from the Military Archive, the corresponding periodicals and literature.